Increased substitution rates surrounding low-complexity regions within primate proteins. - Lenz, C; Haerty, W; Golding, G (Oxford University Press, 2014)
Previous studies have found that DNA-flanking low-complexity regions (LCRs) have an increased substitution rate. Here, the substitution rate was confirmed to increase in the vicinity of LCRs in several primate species, including humans. This effect was also found among human sequences from the 1000 Genomes Project. A strong correlation was found between average substitution rate per site and distance from the LCR, as well as the proportion of genes with gaps in the alignment at each site and distance from the LCR. Along with substitution rates, dN/dS ratios were also determined for each site, and the proportion of sites undergoing negative selection was found to have a negative relationship with distance from the LCR.